2017
DOI: 10.1108/aaaj-01-2015-1953
|View full text |Cite
|
Sign up to set email alerts
|

Accountants and the professional project

Abstract: Purpose The purpose of this paper is to offer a critique of the sociological model of professionalisation known as the “professional project” put forward by Magali Larson, which has become the prevailing paradigm for accounting historians. Design/methodology/approach The paper challenges the use of the concepts of monopoly, social closure, collective social mobility and the quest for status as applied to the history of accountancy. The arguments are made on both empirical and theoretical grounds. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Larson, 1977). On the contrary, our research, in line with Matthews (2017), is a case of “non”-closure or ring-fencing around the expertise (and the tool) created. Our study emphasizes how a professionalization project where the expertise was constantly extended to a wider network foster the emergence of a profession.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Larson, 1977). On the contrary, our research, in line with Matthews (2017), is a case of “non”-closure or ring-fencing around the expertise (and the tool) created. Our study emphasizes how a professionalization project where the expertise was constantly extended to a wider network foster the emergence of a profession.…”
Section: Discussionmentioning
confidence: 97%
“…In the past, the accounting professionalization literature has drawn extensively on the notion of "closure" and monopoly around a new professional project concept, insisting on the need to exert control over knowledge (eg, Larson, 1977). On the contrary, our research, in line with Matthews (2017), is a case of "non" closure or ring-fencing around the expertise (and the tool) created. Our study emphasizes how a professionalization project where the expertise was constantly extended to a wider network foster the emergence of a profession.…”
Section: Creative Work Knowledge Work and Boundary Work: Discussing Tmentioning
confidence: 96%
“…Thus, whilst the accountancy profession has limited social mobility, the reality does not appear to be as extreme as is often portrayed. Lee (2004) and Matthews (2017) showed that around a third of the earliest chartered accountants had experienced upward, vertical, inter-generational social mobility. A contribution of this paper is the finding that this situation appears to have largely persisted over time with 2009 cohort not being substantially different from the earliest ones.…”
Section: Discussionmentioning
confidence: 99%
“…The Institute of Chartered Accountants of Scotland was formed in 1951 by amalgamating the Society of Accountants in Edinburgh with the Institute of Accountants and Actuaries in Glasgow (founded in 1853) and the Society of Accountants in Aberdeen (founded in 1867). providing a more nuanced picture of the early profession than some other literature suggests (Lee 2004, Matthews 2017.…”
Section: The Icas Contextmentioning
confidence: 96%
“…Jacobs’ () study of the Big 5 firms in Scotland found class disadvantages were further perpetuated with a growing focus on non‐technical skills in graduate applicants. Matthews (: 313), however, criticises the notion of social closure in the accounting profession and draws on evidence which suggests ‘accountancy seems to have been more socially open than the business elite generally’.…”
Section: Introductionmentioning
confidence: 99%